PAK KADUK’S NARRATIVE IN MALAYSIAN POLITICAL NEWS: A PRAGMATIC ANALYSIS - Muhammad Zaid, Daud; Mary Fatimah, Subet; Awang Azman, Awang Pawi (Jilin University, 2023)
Pak Kaduk (PK) is one of the characters in Malay jokes. PK's character is described as a negative character, and due to this, the society associates PK's character and narrative with the political situation in Malaysia. Therefore, this study will analyze the character and narrative of PK in political news in Malaysia. This study adopts a qualitative method (or specifically, the document analysis method). The theory used for this study is the Relevance Theory (Sperber & Wilson, 1986, 1995) in the pragmatic field. In Pak Kaduk's funny anecdotes and jokes, there are six narratives, namely: (1) about his dressing etiquette (PK’s paper shirt), (2) regarding the connection of the PK’s chicken with the sultan/king, (3) about PK’s nutrition (cold rice), (4) about PK paddling a canoe, (5) about PK killing his wife and (6) regarding PK migrating or leaving the village. The results of the study found that a total of 13 pieces of political news linked PK's narrative and character with the political situation in Malaysia. In conclusion, this study can prove that the character of PK is not only studied in the field of literature and linguistics but can even be associated with the context raised in this current work (politics in Malaysia).